A swiftly tilting planet - L'Engle, Madeleine (New York : Square Fish/Farrar, Straus and Giroux, 1978)
The youngest of the Murry children must travel through time and space in a battle against an evil dictator who would destroy the entire universe.
Keywords: Science fiction